2013
DOI: 10.1016/j.jviscsurg.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal sinus disease

Abstract: Pilonidal disease is a frequent suppurative condition that occurs twice as often in men as in women, usually between the ages of 15 and 30. Pilonidal disease is located beneath the skin of the sacro-coccygeal region. It presents acutely as an abscess under tension while the chronic form gives rise to intermittent discharge from pilonidal sinus(es). Diagnosis is clinical and usually straightforward. In the large majority of cases, treatment is surgical but there is no consensus as to the 'ideal' technique. Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
147
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 51 publications
2
147
0
8
Order By: Relevance
“…In such circumstances, the wound should be dressed daily, and infection development should be avoided (de Parades et al, 2013). With the marsupialization technique in which the edges of the wound are sutured, the injury is minimized, and this fastens the healing process (Mentes et al, 2004a).…”
Section: Lay Openmentioning
confidence: 99%
See 1 more Smart Citation
“…In such circumstances, the wound should be dressed daily, and infection development should be avoided (de Parades et al, 2013). With the marsupialization technique in which the edges of the wound are sutured, the injury is minimized, and this fastens the healing process (Mentes et al, 2004a).…”
Section: Lay Openmentioning
confidence: 99%
“…With the marsupialization technique in which the edges of the wound are sutured, the injury is minimized, and this fastens the healing process (Mentes et al, 2004a). In recent years, various dressings and negative pressure wound care products are preferred (de Parades et al, 2013).…”
Section: Lay Openmentioning
confidence: 99%
“…However, pilonidal abscesses are routinely managed with incision and drainage of the fluctuant swelling accompanied by washout and leaving the wound open for healing by secondary intention. 4 The postoperative course of patients undergoing incision and drainage is associated with prolonged wound healing time, pain, regular wound dressing and delayed return to daily activities. In 2011, Meinero described a novel technique using a fistuloscope for the treatment of anal fistulae.…”
Section: Introductionmentioning
confidence: 99%
“…Hair strands grow beneath the skin, leading to local inflammation, the foreign body reaction and infection. 3 Treatment for acute PD consists of abscess incision and drainage. The chronic form can be managed in many ways, from removal of all the infected tissue or only unroofing the pilonidal sinuses, leaving the wound open to heal by secondary intention before using plastic surgery techniques such as a Karydakis flap (KF) or Limberg flap (LF).…”
mentioning
confidence: 99%
“…The chronic form can be managed in many ways, from removal of all the infected tissue or only unroofing the pilonidal sinuses, leaving the wound open to heal by secondary intention before using plastic surgery techniques such as a Karydakis flap (KF) or Limberg flap (LF). 3 The authors of a meta-analysis of 25 trials (2,949 patients) suggested that open radical excision and primary midline closure should be abandoned in favor of sinusotomy/sinectomy or en bloc resection with off-midline primary closure. 4 The authors of the present article performed radical excision with primary midline closure before the introduction of the Dufourmentel modification of the Limberg flap (DMLF), but the outcomes were poor, especially in patients with PD and laterally localized sinuses.…”
mentioning
confidence: 99%